2010
DOI: 10.1159/000314138
|View full text |Cite
|
Sign up to set email alerts
|

Sun-Induced Changes in Stratum Corneum Function Are Gender and Dose Dependent in a Chinese Population

Abstract: Previous studies have demonstrated that UVB radiation changes the epidermal permeability barrier and stratum corneum (SC) hydration. It is well known that sun exposure causes erythema, sunburn and melanoma. However, whether daily sun exposure alters SC integrity and epidermal permeability barrier function is largely unknown, especially in Chinese subjects. In the present study, we assess the SC integrity, SC hydration and epidermal permeability barrier function following various doses of sun exposure. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 98 publications
4
25
0
Order By: Relevance
“…This is consistent with the body site comparison work of photoprotected and photoexposed forearms of subjects living in the U.S.A. . Photoexposed Chinese subjects, however, have been reported to have elevated basal TEWL levels on their volar forearms . In both of these reported studies, it is expected that the body sites will be more melanised, but there was no reported increase in skin barrier function.…”
Section: Discussionsupporting
confidence: 83%
“…This is consistent with the body site comparison work of photoprotected and photoexposed forearms of subjects living in the U.S.A. . Photoexposed Chinese subjects, however, have been reported to have elevated basal TEWL levels on their volar forearms . In both of these reported studies, it is expected that the body sites will be more melanised, but there was no reported increase in skin barrier function.…”
Section: Discussionsupporting
confidence: 83%
“…Measurements were taken on the left dorsal hand, left canthus and forehead with a Corneometer CM825 attached to a Courage‐Khazaka MPA5 system (CK electronic GmbH, Koeln, Germany) (2, 32). For the SC rehydration study, a moisturizer containing petrolatum, glycerol and propylene glycol was applied to the measured sites immediately after the initial hydration measurement.…”
Section: Methodsmentioning
confidence: 99%
“…UB radiation‐caused immunosuppression is greater in males than in females (30) and the number of UVB‐induced skin tumors is more in males than in females (31). Similarly, following lower doses of sun exposure, barrier recovery is faster in females than in males (32). Although previous studies demonstrated some gender difference in sun exposure‐induced changes in SC hydration, its association with age and gender is not well delineated as yet.…”
mentioning
confidence: 99%
“…Skin surface temperature and sweating additionally alter TEWL (Pinnagoda et al, 1990). Studies have also shown seasonal variation in TEWL and that TEWL is affected by circadian rhythm and sun exposure (Le Fur et al, 2001;Liu et al, 2010).…”
Section: Summary Pointsmentioning
confidence: 99%